FORMATION METHODOLOGY OF AN INTERACTIVE LEARNING ENVIRONMENT IN TEACHING SCIENCE BASED ON KAHOOT, GENIALLY AND WORDWALL PLATFORMS (European Journal of Interdisciplinary Research and Development, 2025)
This article scientifically and methodologically examines the issues of organizing the educational process effectively in science lessons through digital interactive platforms such as Kahoot, Genially, and Wordwall. During the study, the influence of these platforms on increasing students’ learning activity, strengthening motivation, and developing cognitive skills was analyzed. Experimental observations showed that systematic use of these resources increased students’ engagement in lessons by 28–35% and improved topic mastery indicators by 15–22%. In addition, the article presents practical results on specific methodological approaches to lesson design, interactive task creation, and lesson scenario development. The article is intended for teachers, researchers in pedagogy, educational technology, and methodology, as well as educational institutions aiming to implement STEAM-based and modern digital teaching platforms. The material is suitable for use in covering topics related to science education, STEAM integration, digital pedagogy, and interactive teaching methods.